(untitled) (Nigerian Journal of Physiological Sciences, 2020)
Intestinal Ischaemia-Reperfusion Injury as distinct from Ischaemia-Reperfusion Injury is what occurs when blood supply to the intestines is cut off either inadvertently in some gastrointestinal emergencies or during abdominal surgical interventions. The phenomenon leads to formation of reactive oxygen species and subsequent up-regulation upon reaching the spleen and consequent effects in organs of the body such as increased sperm cell abnormalities. The changes which occur in the intestine and some distant organs due to remote effects of intestinal ischaemia-reperfusion have been demonstrated but there is paucity of information on these effects on the testes with implications on fertility which was investigated in this study. Fifteen adult male Wistar rats were used for this study. Group A was the control in which a sham laparatomy was done, Group B, in which intestinal ischaemia- reperfusion was set up and C in which splenectomy was done before setting up intestinal ischaemia-reperfusion by clamping the superior mesenteric artery. The ishaemia was for an hour and reperfusion also for an hour. Following reperfusion, portions of the intestines, epididymis and testes were harvested. Histomorphometry of intestines revealed a villus height of 93.98µm, 91.44µm, and 110.48µm in control, intestinal ischaemia-reperfusion and splenectomised rats and villi width of 24.5µm, 24.6µm and 38.5µm respectively. Testicular histomorphometry revealed seminal tubular diameter as189µm, 197µm and 215µm and luminal diameter of 58µm, 59µm and 62µm. Histopathology revealed congestion, desquamation and defoliation of germinal epithelium in all three groups but control rats had sperm cells present. In IIR group tubular damage and oedema were present and sperm cells were absent but in splenectomised rat, sperm cells were present in some tubules and absent in others but no tubular damage was observed. Splenectomy does exert a protective effect on intestinal ischaemia-reperfusion by moderating the effects in remote organs, as seen in testes